Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jfd.12916
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid changes in the capsid protein of a reassortant betanodavirus strain: Effect on viral replication in vitro and in vivo

Abstract: Betanodavirus reassortant strains (RGNNV/SJNNV) isolated from Senegalese sole harbour an SJNNV capsid featuring several changes with respect to the SJNNV‐type strain, sharing three hallmark substitutions. Here, we have employed recombinant strains harbouring mutations in these positions (r20 and r20 + 247 + 270) and have demonstrated that the three substitutions affect different steps of the viral replication process. Adsorption ability and efficiency of viral attachment were only affected by substitutions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…NNV replication is a temperature‐sensitive process regulated mainly by RNA1 (Hata et al., 2010; Panzarin et al., 2014; Souto et al., 2019). Optimal temperatures for the in vitro growth of the genotypes found in Southern Europe range from 20 to 30°C (Iwamoto et al., 2000; Panzarin et al., 2014), which also seem to correlate with the onset of epizootic outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…NNV replication is a temperature‐sensitive process regulated mainly by RNA1 (Hata et al., 2010; Panzarin et al., 2014; Souto et al., 2019). Optimal temperatures for the in vitro growth of the genotypes found in Southern Europe range from 20 to 30°C (Iwamoto et al., 2000; Panzarin et al., 2014), which also seem to correlate with the onset of epizootic outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum temperature for virus multiplication ranges from 15 °C to 30 °C depending on NNV genotypes and upper limit temperatures range from 32 °C to 35 °C. It has been reported that these temperatures mainly depend on genomic RNA1 which encodes RNA polymerase, although genomic RNA2 coding for CP also plays a role 3034 . Infectivity of NNV gradually declines at 37 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that, whether all mutant viruses were infective, mutants showing single mutations (at 245 or 270 amino acid residues, but not both) reduced mortality rates in a 37% or 60% in turbot ( Scophthalmus maximus ) or Senegalese sole, respectively, but highest survival rate was observed in fish infected with the double mutation (at 245 + 270) 63,69,70 . Moreover, in primary cultures of Senegalese sole neurons, all isolates tested (RGNNV, SJNNV and RGNNV/SJNNV) were able to infect and replicate into the cells whilst the recombinant virus with modifications at both 247 and 270 amino acid residues delayed the viral replication, as well as happens in the brain tissue 71,72 . Certainly, the different amino acid residues changes, including an additional shift at residue 20, appear to be involved in different steps of the viral replication such as the adsorption ability and efficiency of viral attachment, viral binding or particles budding 71 .…”
Section: Pathogenicity and Host‐specificity Of Nnv Reassortantsmentioning
confidence: 99%
“…63,69,70 Moreover, in primary cultures of Senegalese sole neurons, all isolates tested (RGNNV, SJNNV and RGNNV/SJNNV) were able to infect and replicate into the cells whilst the recombinant virus with modifications at both 247 and 270 amino acid residues delayed the viral replication, as well as happens in the brain tissue. 71,72 Certainly, the different amino acid residues changes, including an additional shift at residue 20, appear to be involved in different steps of the viral replication such as the adsorption ability and efficiency of viral attachment, viral binding or particles budding. 71 Moreover, soles infected with the attenuated mutant (mutation affecting at 245 and 270 residues) exerted down-regulated antiviral immune responses at transcriptional level, 69 demonstrating the crucial role of these residues in the virulence of NNV.…”
Section: Pathogenicity and Host-specificity Of Nnv Reassortantsmentioning
confidence: 99%
See 1 more Smart Citation